VAGINAL HYSTERECTOMY AMENDED BY THE TECHNICAL PELOSI. PRELIMINARY REPORT - Coripuna, Italo (2015)
OBJECTIVE: To understand the benefits of implementing a new surgical technique to marginal hysterectomy. DESIGN: Cross-sectional study. PLACE: Cayetano Heredia National Hospital. MATERIALS AND METHODS: Patients implanted with the surgical technique of vaginal hysterectomy amended by Pelosi, between June 1998 and May 2001. RESULTS: Eighty-seven percent of interventions was conducted by the resident. The average time of surgery was 122 minutes. A womb of up to 18 cm was extracted. There were no intraoperative complications and postoperative complications were urinary tract infection (13%) and infection dome (8.7%). In the histopathological analysis, the most common finding was chronic cervicitis (35%). CONCLUSIONS: vaginal hysterectomy by Pelosi modified technique is a safe procedure that shows in our environment similar to those reported in the literature benefits.